Toto Orthography Development - Anderson, Toby; Evans, Jonathan P (Nepalese Linguistics, 2024)
The Toto orthography, developed beginning in 2014, was created to address the inadequacies of using Bengali and Latin alphabets for writing Toto. These scripts failed to represent certain phonological features, such as front-rounded vowels and breathy vowels, posing challenges for accurate writing. The newly designed orthography, reflecting community input, unambiguously represents Toto phonology. Development of this writing system supports cultural identity, promotes literacy, and aids in educational efforts. Despite standardization, several challenges remain, such as transcribing elision, standardizing word breaks, long vowels, numbers and math symbols, punctuation, etc.